Trend of phubbing behavior researches in Indonesian journals: a content-analysis - Yola Eka Putri; Ifdil Ifdil; Berru Amalianita; Linda Fitria (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
The emergence of mobile technology has led to significant transformations in communication. Nevertheless, it has also presented new challenges, notably exemplified by a phenomenon termed as